Rice-fish co-production pathways for sustainable development in Cambodia - Freed, Sarah; Ou, Phichong; Sean, Vichet; Sun, Vathanak (WorldFish, 2024)
Rice and fish are longstanding staple foods in Cambodia. The wild fish and other aquatic animals in rice field ecosystems are managed as rice field fisheries (RFFs). Well-managed community fish refuges (CFRs) support their productivity and provide a year round aquatic habitat that is well connected to adjacent rice fields. These CFR-RFF systems provide benefits to rural communities that are not easily replaced, including supporting food and nutrition security and supplementary livelihoods. However, pressures from infrastructure development and increasing multisectoral demands on water, food and energy threaten these systems. Although it is essential to maintain CFR-RFF contributions to Cambodia’s rural development, investment in complementary innovations could further advance the country’s sustainable development objectives. This brief outlines the demonstrated benefits of CFR-RFFs, the results from past investment and complementary innovations, and the potential benefits of additional such innovations. The selected innovations are drawn from experiences in Cambodia and elsewhere in South and Southeast Asia, focusing on those with the greatest potential to complement the benefits of CFR-RFFs.